Racial disparity in atherosclerotic cardiovascular disease in hospitalized patients with diabetes 2005-2015: Potential warning signs for future U.S. public health - Gursukhmandeep Singh Sidhu; Charisse Ward; Keith C. Ferdinand (Elsevier, 2020)
Introduction: The pattern of atherosclerotic cardiovascular disease (ASCVD) and diabetes driven hospitalizations in the United States (U.S.) is unclear. We attempted to identify the disparate outcome in race related ASCVD hospitalizations with comorbid diabetes. Methods: Adults aged ≥40 years old with ASCVD (acute coronary syndrome (ACS), coronary artery disease (CAD), stroke, or peripheral arterial disease (PAD)) as the first-listed diagnosis with comorbid diabetes as a secondary diagnosis were determined using the U.S. 2005-2015 National (Nationwide) Inpatient Sample (NIS) data. The incidence of other modifiable cardiovascular risk factors (hypertension, dyslipidemia, smoking/substance abuse, obesity, and renal failure), in hospital procedures and outcomes was estimated. Complex samples multivariate regression was used to determine the odds ratio (OR) with 95% confidence Interval (CI) of risk associations and to determine patient comorbidity adjusted ASCVD related in-hospital mortality rate. Results: The rate of total ASCVD hospitalizations with comorbid diabetes adjusted to the U.S. census population increased by 5.7% for black men compared to 4% for black women. There was a higher odd of an ASCVD hospitalization if there was comorbid hypertension (Odds Ratio (OR 1.29; 95% CI 95% 1.28-1.31), dyslipidemia (OR 2.03; 95% CI 2.01-2.05), renal failure (OR 1.84; 95% CI 1.82-1.86), and smoking/substance use disorder (OR 1.31; 95% CI 1.29-1.33). White Women had the highest risk-adjusted incidence of ASCVD related in-hospital mortality (4.2%) relative to black women (3.9%), compared to white men (3.6%) and black men (3.5%) respectively. Conclusions: Despite improving treatment options for ASCVD in the diabetic population, blacks with diabetes continue to have a higher hospitalization burden with a concomitant disparity in comorbid presentation and outcome. Further evaluation is the need to understand these associations.